Shaping Entrepreneurial Mindsets Innovation and Entrepreneurship in Leadership Development - Canals, Jordi.; Canals, Jordi. (IESE Business Collection, 2015)
Corporate innovation and entrepreneurship are more important than ever to create and sustain growth opportunities. This book deals with the challenge of how to speed up innovation and entrepreneurial initiatives to sustain corporate growth, by focusing on developing the necessary leadership competencies.